ANALYSIS ON THE MUDHARABAH CALCULATION OF IMPROVEMENT REVENUE TRADERS IN BMT BENING ATI GROBOGAN DISTRICT - Tida, Khusnamah (Accounting, 2010)
The existence of an existing conventional bank interest rate system put in operation, while the Islamic Bank are not familiar with the term of interest but is a term used for the results. Banking with profit-sharing system designed by involved unity in the risks and share the results of operations between the owner of the funds that keep their money in the bank, with banks and fund managers as well as people who need funds that can be status as a borrower or a fund manager.With financing coupled with capital management and business guidance to help increase business productivity, which in turn will affect the increased income of small traders. This is the basis for the author to take the title "analyst Mudharabah calculation of income trader at BMT Bening Ati Grobogan district." The purpose of this study is to describe and analyze the effect of increasing revenue Mudharabah traders in District Grobogan.The population of this study is the customer who received BMT Bening Ati Mudharabah, whose population amounted to all customers, totaling 100 samples (40 data can be processed) and the sampling technique using a proportional cluster random sampling technique. The data collection method used is the questionnaire method and documentation. Methods of data analysis used in this research is simple regression analysis of predictors. The results showed that by calculating the correlation coefficient between variables X and Y variables in r hits at 10.500 and table is 1.98, which means there is a relationship between increased revenue Mudharabah against small traders. From the simple regression equation obtained Y = 4.987 X 1.215, while the hypothesis tests performed with T test t obtained for 10.500 hits, which means that said that Ha is the effect of financing to increase the income of traders District Grobogan "acceptable". Based on the above conclusions, the authors convey suggestions include the need for further research on the variables that influence the increase in revenues of the available employment opportunities, skills and expertise, motivation and tenacity to work. Keyword : Mudharabah, Trader, Calculation